Entrepreneurship and Technological Transfer: an analysis of the activity of Amazon business incubators - Oliveira, Márcio Luis de (2019)
Technology transfer (TT) is a process of knowledge exchange and technological skills between firms. There are several instruments for enabling TT, including business incubators, organizations whose mission is to strengthen the entrepreneurial culture, associated with the innovation policy of the STI’s. This paper aimed to analyze how the incubators of Amazonian companies act to support the process of transfer of technologies developed by the enterprises they incubate. The approach was qualitative and quantitative way, with study of cases. Incubators members of the National Association of Innovative Enterprises Promoting Entities (ANPROTEC) were used as a reference.The institutional websites of incubators have little detailed how the processes of support for technology transfer work and the description of trading, valuation and technological readiness (TRL). A point identified was the use of partnerships in the TT process as a solution to the lack of human and financial resources of Amazonian STI’s.